TRADING HOUSES: PROMOTE, DEVELOP AND EXPAND INDONESIAN COOPERATIVES AND SMALL MEDIUM ENTERPRISES - Idris Gautama So (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
Indonesian Cooperatives and Small and Medium Enterprises (SMEs) need to be promoted, developed and expanded, one of the reasons is that cooperatives and SMEs are known as an important post of Indonesian Economics. It is proven in 1998, when multi-dimension crisis hit the country, many of big enterprises collapsed but Cooperatives and SMEs survived. This research is intended to elaborate weaknesses of Cooperatives and SMEs in developing and expanding themselves. Many reasons will be stated and ways to cope with the reasons will be explained. One of the answers is Trading House. Why and how trading houses can help Indonesian Cooperatives and SMEs to develop and expand themselves and how to use trading house in Networking Cooperatives and SMEs to global business will be explained. Success stories of developed countries make trading houses contribute to develop and expand SMEs in their countries will also be shown to figure out how trading houses in these countries contribute to each country. Some suggestions and conclusions will be made in the end of this research.